Computed tomography imaging practice patterns in adult chronic rhinosinusitis: survey of the American Academy of Otolaryngology–Head and Neck Surgery and American Rhinologic Society membership. Issue 6 (23rd April 2015) - Batra, Pete S.; Setzen, Michael; Li, Yan; Han, Joseph K.; Setzen, Gavin
<x xml:space="preserve">Abstract</x> Background The objective of this study was to assess the current practice patterns of computed tomography (CT) imaging for diagnosis and management of adult chronic rhinosinusitis (CRS). Methods A 29‐item, electronic, Web‐based physician survey was disseminated to the American Academy of Otolaryngology–Head and Neck Surgery (AAO‐HNS) and American Rhinologic Society (ARS) membership from November 2012 to January 2013. Results A total of 331 otolaryngologists completed the survey. Seventy‐five percent of respondents did not obtain confirmatory CT imaging prior to initiating medical therapy for CRS. A typical diagnostic scan was considered to be a 3‐mm coronal CT with or without 3‐mm axial images for 50.6% of participants. On average, the respondents obtained 1 (58.8%) or 2 (36.6%) CT scans prior to proceeding with sinus surgery. CT scanning was most commonly performed in a hospital radiology department (76.4%), followed by a free‐standing imaging center (44.5%). An in‐office CT scanner was owned by 24.5% of the respondents, mostly commonly a cone beam CT (74.0%) scanner. Most respondents (87.1%) did not experience problems with carriers denying ability to image or reimbursing for scans. Overall, 68.4% of the respondents were unaware of the dosage of radiation delivered by the scanner used for CT acquisition. Conclusion This survey provides a snapshot of the current utility of CT imaging in the management paradigm for CRS. Given that most are unaware of the delivered radiation dose, this clearly represents an important area of improvement in the knowledge gap.